Tuning the interfacial property of hierarchical composites by changing the grafting density of carbon nanotube using 1,3-propodiamine - Li, Yuxin (2013)
Carbon nanotubes (CNTs) were chemically grafted onto carbon fiber (CF) by 1,3-propodiamine bridging. The grafting density could be tuned by reaction time and concentration of 1,3-propodiamine. The fourier transform infrared spectra and X-ray photoelectron spectroscopy confirmed the chemical bonding nature between CNT and CF. The interfacial shear strength of the hierarchical composites is highly dependent on the grafting density, which could be two times that of as-received composite. The interfacial enhancement mechanism was also analyzed.